Dampak Media Sosial Shopee Terhadap Pendapatan Bisnis Online - Rowiyani, Rowiyani; Mahiruna, Adiyah; Soleh, Khoerul; Robeth Suprayitno, Muhammad; Maira Cahaya Putra, Bintang (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The development of information and communication technology, especially the internet and social media, has brought significant changes to various aspects of life, including the business world. The internet has become a vital platform for running an online business, providing easy access to information and expanding market reach without geographic limitations. One social media platform that is increasingly popular in supporting online businesses is Shopee. This research aims to examine how using Shopee can increase income for online business people in Amposari Village, Pedurungan District, Semarang City. The method for carrying out this research includes preparation stages, training implementation, and evaluation. Training activities were carried out by lecturers and students of the Muhammadiyah Semarang Institute of Statistics and Business Technology for one month in March 2024. The training participants were Dasa Wisma women who were involved in various sectors such as agriculture, animal husbandry, and waste management. The training uses lectures, discussion, and question-and-answer methods to explore participants' ideas or opinions about online business development and increasing digital literacy. The research results showed that the participants were very cooperative and enthusiastic in all training activities. There are no significant obstacles that hinder the implementation of activities. The training material on Shopee social media was well received by participants, with 80% of participants understanding the content of the material presented. This training improved participants' abilities in optimizing business through social media, especially Shopee, and fostered an entrepreneurial spirit to improve people's lives. The conclusion of this research shows that Shopee has a significant influence on increasing online business revenue and offers great potential for new and established businesses. However, further research is needed to explore the most effective strategies for utilizing Shopee features to maximize revenue.